The Original Homeland of the Slavs Praojczyzna Słowian - Mańczak, Witold (Studia mythologica Slavica, 2009)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In the late seventies, the author proposed a new method of linguistic and ethnogenetic research, namely, the method of comparing the vocabulary in parallel texts. Using this method, he examined relationships between different languages (Gothic, Old Church Slavic, and Lithuanian; German, Polish and Lithuanian; Polish, Old Prussian, and Lithuanian, etc.) and finally arrived at the conclusion that the original homeland of the Slavs was in the basin of the Oder and the Vistula rivers.